Yosua Sebagai Model Hamba Tuhan Dalam Suksesi Kepemimpinan - puji swismanto (Sekolah Tinggi Teologi Nusantara, 2021)
Abstract:The purpose of this research is to describe that leadership in an institution continues to be sustainable, and a leader must also be ready to be replaced and prepare a substitute for the continuity of the institution being led. However, the fact is that there are many leaders who are not willing to leave their chairmanship and do not prepare a replacement leader. A leader must realize that the age and age factor cannot be denied and inevitably must be ready to be replaced and appoint a substitute. Two Old Testament Bible characters who can serve as models for God's servants in leadership succession. Joshua's point of departure and model provides the reason that Joshua has had a high attitude and character and integrity as a leader and is ready to accept the leadership relay as a substitute for Moses. So that in this work the author focuses on Joshua, as a substitute for the qualitative description method used. focuses on the object of research on the book of Joshua and supporting literature review. To get good results the researcher used descriptive qualitative methods by examining literature research with the main source of the Book of Joshua and supported by the biblical text which is very close to the discussion by describing Joshua as a model of God's servant in leadership succession. The results found from this research are that Moses and Joshua as God's servants have carried out a succession of leadership for the sake of the people who are led in achieving their goals. Abstrak:Tujuan penelitihan ini untuk mendikripsikan bahwa Kepemimpinan dalam sebuah embaga terus berkelanjutan, dan seorang pemimpin juga harus siap untuk digantikan dan mempersiapkan penganti demi kelangsungan lembaga yang dipimpin. Namun fakta yang terjadi tidak sedikit pemimpin yang tidak rela meninggalkan kursi kepemimpinanya dan tidak mempersiapkan seseorang pemimpin pengganti, Seorang pemimpin harus menyadari akan dirinya bahwa masa dan faktor usia tidak dapat dipungkiri dan mau tidak mau harus siap digantikan dan menunjuk penggati. Dua tokoh Alkitab Perjanjian Lama yang dapat diteladani sebagai model bagi hamba Tuhan dalam suksesi kepemimpinan. Titik tolak dan model pada diri Yosua memberikan alasan bahwa Yosua telah memilki sikap dan karakter dan intergitas yang tinggi sebagai seorang pemimpin dan siap menerima estafet kepemimpinan sebagai penggati Musa. sehingga dalam karya ini penulis terfokus pada diri Yosua,sebagai pengganti.dengan metode diskripsi kualitatif yang berfokus pada obyek penelitian kitab Yosua dan kajian pustaka yang mendukung. Untuk mendapatkan hasil yang baik peneliti mengunakan metode kualitatif diskriptif dengan meneliti penelitihan literatur dengan sumber utama KitabYosua dan ditunjang dengan teks Alkitab yang erat sekali dengan pembahasan dengan cara mendiskripsikan Yosua sebagai Model hamba Tuhan dalam suksesi kepemimpinan. Hasil yang ditemukan dari peneliti ini Musa dan Yosua sebagai hamba Tuhan telah melaksanakan suksesi kepemimpinan demi umat yang dipimpin dalam mencapai tujuan.